Pembuktian Teorema Van Aubel - Saufi Zikri (PT PUSTAKA CENDEKIA GROUP, 2023)
In learning mathematics, geometry is divided into two parts, namely plane geometry and space geometry. The main focus in plane geometry lies on points, lines, planes, and angles. In plane geometry, Van Aubel's theorem explains the relationship between the squares built on each side of the quadrilateral. Van Aubel's theorem was first put forward by Henri Van Aubel in 1878. Van Aubel's theorem is constructed from an arbitrary quadrilateral, then a square is built on each side of an arbitrary quadrilateral, the points of intersection of the diagonals of the squares on each opposite side are connected so that two lines are the same length and intersect perpendicularly. In general, Van Aubel's theorem is constructed from any plane convex quadrilateral.